Contribuiç\~oes teóricas para o direito e desenvolvimento - Patrícia Borba Vilar Guimar\~aes (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– This paper deals with the analysis of the doctrinal foundations of Law and Development (D&D) regarding to the need to support future research and applications of the subject in national and international context. The characterization of the scientific autonomy of the D&D was intended through the delimitation of its historical background and conceptual doctrine, also in domestic and foreign conditions, and the relationship between law and development, according to its history. A propaedeutic conceptualization of law and development was made, as though as an interrelation between D&D and New Developmentalism (ND). Texts were selected between the most significant authors of our time in this field, by means of an interdisciplinary approach, bringing together elements of Law, Economics, Sociology and Political Science, aiming to propose some theoretical spaces for discussion and analysis of the function, characteristics and conditions approaches to law and development in contemporary societies.
Keywords: K00; 330; law and development; law and development history; national development; Entwicklung; Rechtsordnung; Rechtsökonomik